2012
DOI: 10.1007/s11999-011-2240-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Using Bisphosphonate to Treat Legg-Calvé-Perthes Disease

Abstract: Background The rationale for using bisphosphonate (BP) therapy for Legg-Calvé-Perthes disease (LCPD) is the potential to prevent substantial femoral head deformity during the fragmentation phase by inhibiting osteoclastic bone resorption. However, it is unclear whether BP therapy decreases femoral head deformity. Questions/purposes In this systematic review, we answered the following questions: (1) Does bisphosphonate (BP) therapy decrease femoral head deformity and improve pain and function in LCPD or other j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
0
30
0
2
Order By: Relevance
“…The rationale for using bisphosphonates in LCPD is their action on inhibiting osteoclastic bone resorption, thereby potentially preventing femoral head deformity. A systematic review of studies on bisphosphonates in LCPD concluded that there is lack of clinical evidence to say that bisphosphonates decrease femoral head deformity in LCPD, however, all studies noted subjective improvement of pain and gait in patients [25]. Only in one study, bisphosphonates were started before the stage of collapse of osteonecrosis and syndrome, or those associated with skin manifestations such as SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis and osteitis) lie along the CRMO spectrum with different levels of severity.…”
Section: Leg-calve-perthe's Disease (Lcpd)mentioning
confidence: 99%
“…The rationale for using bisphosphonates in LCPD is their action on inhibiting osteoclastic bone resorption, thereby potentially preventing femoral head deformity. A systematic review of studies on bisphosphonates in LCPD concluded that there is lack of clinical evidence to say that bisphosphonates decrease femoral head deformity in LCPD, however, all studies noted subjective improvement of pain and gait in patients [25]. Only in one study, bisphosphonates were started before the stage of collapse of osteonecrosis and syndrome, or those associated with skin manifestations such as SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis and osteitis) lie along the CRMO spectrum with different levels of severity.…”
Section: Leg-calve-perthe's Disease (Lcpd)mentioning
confidence: 99%
“…[44] Ancak klinik kanıtların halen yetersiz olması nedeniyle Perthes hastalığında kullanımı önerilmez. [45] BMP'ler (bone morphogenic protein) ile bifosfonatların kemik onarımında sinerjik etkilerinin olduğu bilinir. [20] Lokal ibandronat uygulaması ile birlikte BMP-2'nin uygulandığı bir hayvan deneyinde, kontrol grubuna göre femur başı deformitesinin daha az ve trabeküler kemik miktarının daha fazla olduğu gösterilmiştir.…”
Section: Perthes Hastaliğinda Gelecek Tedavi̇si̇unclassified
“…One could attempt to inhibit bone resorption by using bisphosphonates, 22 or RANKL inhibitors. One could attempt to inhibit bone resorption by using bisphosphonates, 22 or RANKL inhibitors.…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…[25][26][27] Biological treatments for models of Perthes disease in animals appear promising, 28,29 but human clinical evidence is not yet available. [25][26][27] Biological treatments for models of Perthes disease in animals appear promising, 28,29 but human clinical evidence is not yet available.…”
Section: Emerging Therapiesmentioning
confidence: 99%